Immunochemical studies of conjugates of isomaltosyl oligosaccharides to lipid. I. Antigenicity of the glycolipids and the production of specific antibodies in rabbits (The Rockefeller University Press, 1981)
Isomaltose oligosaccharides varying in size from two sugars, isomaltose (IM2), to seven sugars, isomaltohepatose (IM7), were coupled to stearylamine by reductive amination with sodium cyanoborohydride. Each compound was purified by column chromatography to yield a series of glycolipids containing oligosaccharides differing in length. Stearyl- isomaltotriose to stearyl-IM7 could be incorporated into liposomes and could render them agglutinable by specific antibodies to alpha 1 leads to 6 dextran and could be lysed if complement was also added, whereas those containing stearyl-IM2 were not agglutinated or lysed, indicating that stearyl-IM2 may not be protruding from the liposome surface sufficiently to react with the antibody. Stearyl-isomaltosyl oligosaccharides by themselves or incorporated into liposomes were equally antigenic when emulsified in complete Freund's adjuvant. They elicited pauciclonal responses, and the antibodies were alpha 1 leads to 6 specific, cross-reacted with dextran, and gave semirestricted isoelectric focusing patterns.